2019
DOI: 10.1101/633727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral bacteriophages are maintained at high levels for months in individuals but infrequently transmitted between mothers and infants

Abstract: 14In this work, we exploit recent advances in metagenomic assembly and bacteriophage 15 identification to describe the phage content of saliva from 5 mother-baby pairs sampled 16 twice 7 -11 months apart during the first year of the babies' lives. We identify 25 phage 17 genomes that are comprised of one to 71 contigs, with 16 having a single contig. At the 18 detectable level, phage were sparsely distributed with the most common one being 19 present in 4 of the 20 samples, derived from two mothers and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…176,178 Transmission of oral phages can take place between mother and children, family members, couples with intimate contact and people in the same household. 91,179,181 A study of couples demonstrated common features in the tongue phage population. 91 People who are sharing or have shared households in the past also harbor many phages of same sequences.…”
Section: Reservoir and Transmission Of Oral Phagesmentioning
confidence: 99%
See 2 more Smart Citations
“…176,178 Transmission of oral phages can take place between mother and children, family members, couples with intimate contact and people in the same household. 91,179,181 A study of couples demonstrated common features in the tongue phage population. 91 People who are sharing or have shared households in the past also harbor many phages of same sequences.…”
Section: Reservoir and Transmission Of Oral Phagesmentioning
confidence: 99%
“…180 However, transmission of oral phages between mother and infant have been rarely observed, perhaps due to methodological study limitations. 181 Direct contact, like kissing, 182 or indirect transfer by deposited oral material (eg, food, utensils) or severe coughing are potential routes of phage transmission. Bidirectional transmission of oral phages between people and pets has not been described, but it may occur in the case of close contact or sharing of uten-…”
Section: Reservoir and Transmission Of Oral Phagesmentioning
confidence: 99%
See 1 more Smart Citation